Composite coating electrode and preparation method and application thereof

By adopting a composite coating structure on the titanium electrode, including a titanium matrix and a multi-layer active oxide coating, the existing titanium electrode has solved the problem of high cost and poor corrosion resistance in the zinc electrostatic accumulation industry, and achieved an efficient and corrosion-resistant titanium anode material, which is suitable for the zinc electrostatic accumulation industry.

CN119877044APending Publication Date: 2025-04-25YUNNAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510093834.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing titanium electrodes have problems such as high cost, poor corrosion resistance and short electrode life in the zinc electrostatic accumulation industry. Especially in the acidic oxygen evolution environment, the bonding strength between the coating and the substrate is insufficient, which hinders its industrial application.

Method used

A composite coating structure is adopted, including a titanium matrix, a matrix bonding layer, an intermediate active layer and a surfactant layer. Each layer contains oxides of Ti, Ir, Ru and Co., and is prepared by sol-gel method, sprayed and calcined to form a dense and uniform coating.

Benefits of technology

It improves the current efficiency and corrosion resistance of the titanium anode plate, extends the electrode life and reduces costs, and is suitable for the zinc electrostatic accumulation industry and replaces the traditional lead-silver alloy anode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877044A_ABST
    Figure CN119877044A_ABST
Patent Text Reader

Abstract

The invention discloses a composite coating electrode and a preparation method and application thereof, and belongs to the technical field of titanium electrodes, the composite coating electrode comprises a titanium substrate, a substrate binding layer, a middle active layer and a surface active layer which are stacked, and the substrate binding layer, the middle active layer and the surface active layer all comprise oxides of Ti, Ir, Ru and Co. The preparation method comprises the following steps: respectively preparing a matrix binding layer coating liquid, a middle active layer coating liquid and a surface active layer coating liquid by using a sol-gel method, sequentially coating the matrix binding layer coating liquid, the middle active layer coating liquid and the surface active layer coating liquid on a titanium matrix, and calcining after coating each layer, so as to obtain the titanium-based composite material. And the composite coating electrode is obtained. The proportions of all the layers in the obtained electrode are different, all the metal oxides have different matching effects, the obtained coating is compact and uniform and is not prone to being eroded and stripped, and the current efficiency and corrosion resistance of the titanium anode plate are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium electrodes, and in particular relates to a composite coating electrode and a preparation method and application thereof. Background Art

[0002] At present, most of the anodes used in the zinc electrowinning industry are lead-based alloy anodes. Lead will inevitably dissolve during the electrowinning process, and some of it will be adsorbed or deposited on the cathode zinc sheet, increasing the lead content in the cathode zinc sheet and affecting the quality of zinc. In addition, lead is a toxic heavy metal, and excessive accumulation in the body can cause great harm to the human body.

[0003] Titanium electrodes have the advantages of light weight, good conductivity, strong corrosion resistance, high mechanical strength, and long service life. Their excellent resistance to wet chlorine is unmatched by other metal materials. At present, titanium electrodes with Ir and Ru coatings are the main ones, and the composition and structure of the coating material are one of the most important factors determining the performance of the electrode. Therefore, a large number of researchers want to create a new multi-component coating material and new structure by adding ordinary metals to seek synergistic effects, reduce the use of precious metals such as Ir and Ru, and improve the electrode catalytic activity, but have not achieved a substantial breakthrough. In addition, in most cases, the failure of titanium electrodes is not caused by the loss of electrocatalytic activity of the oxide coating itself, but by the corrosion and passivation of the base metal during operation, the loss of the conductive carrier function, and the large-scale peeling of the coating. Therefore, the bonding strength between the coating and the substrate is another research focus. The chlor-alkali industry has obtained a good solution, but it has not been well solved in the acidic oxygen evolution environment, which hinders its industrial application. The zinc electrowinning process is carried out in a high-acid, oxygen-evolving environment, which is very different from titanium electrodes with Ir and Ru coatings in a wet chlorine environment. Problems such as coating cost, acid corrosion, and bonding between the coating and the substrate all need to be urgently addressed. Therefore, it has not been applied in the zinc electrowinning industry.

[0004] Therefore, how to provide a new type of titanium anode material with low cost, corrosion resistance and long life is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a composite coating electrode and a preparation method and application thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A composite coating electrode comprises a stacked titanium substrate, a substrate bonding layer, an intermediate active layer and a surface active layer, wherein the substrate bonding layer, the intermediate active layer and the surface active layer all comprise oxides of Ti, Ir, Ru and Co.

[0008] More preferably, the oxides of Ti, Ir, Ru and Co specifically include TiO2, IrO2, RuO2 and CoO2.

[0009] Preferably, the molar ratio of Ti:Ir:Ru:Co in the substrate bonding layer is (1.5-3):(0.5-0.7):(0.3-0.5):(0.5-1).

[0010] Preferably, the molar ratio of Ti:Ir:Ru:Co in the intermediate active layer is (1-1.5):(2-3):3:(3-5).

[0011] Preferably, the molar ratio of Ti:Ir:Ru:Co in the surface active layer is (0.3-0.5):5:3:2.

[0012] Beneficial effects: The three-layer active structure of the present invention has the same metal elements but different proportions. The matrix bonding layer of the titanium matrix enhances the bonding strength with the matrix. The intermediate active layer increases the metal Co content as a substitute metal for Ir, which reduces the use of Ir. The surface active layer increases the Ir content and appropriately reduces the use of Co. The intermediate active layer and the surface active layer always ensure that the molar ratio of (Ir+Co):Ru is 7:3, ensuring a high catalytic activity. The change in the metal Ti content is that the closer to the matrix, the higher the content, ensuring that the coating has a strong bonding strength with the matrix, and each layer of the coating can also be tightly bonded to each other. The reduction in the surface Co content is to prevent excessive dissolution of metal Co into the electrolyte and affect the quality of the electrolyte.

[0013] A method for preparing a composite coating electrode comprises the following steps:

[0014] After preparing the substrate bonding layer coating liquid, the intermediate active layer coating liquid and the surface active layer coating liquid respectively by the sol-gel method, the substrate bonding layer coating liquid, the intermediate active layer coating liquid and the surface active layer coating liquid are sequentially coated on the titanium substrate, and calcined after each layer is coated to obtain the composite coating electrode.

[0015] Beneficial effects: The present invention uses the sol-gel method to achieve a fully uniform mixing of effective substances and ensure the uniformity of the coating components; different coating solutions are selected for different coatings to achieve coating structure design, making full use of the effects and characteristics of coatings with different components to achieve the optimal effect of the coating. For example, the bottom coating combined with the titanium substrate is required to be firmly bonded to the titanium substrate, have good conductivity and corrosion resistance, and have good bonding with the middle layer. The middle active layer mainly plays a catalytic role, and as a reaction catalyst, it reduces the reaction energy barrier and improves the reaction efficiency; the surface active layer must not only have good catalytic properties, but also have strong corrosion resistance to ensure the stability of the coating. The present invention designs the coating structure based on the above ideas to prepare a high-performance coated titanium anode.

[0016] Preferably, the coating amount of the substrate bonding layer coating liquid, the intermediate active layer coating liquid and the surface active layer coating liquid before sintering is 1-2 mg / cm 2 , preferably 1.5 mg / cm 2 .

[0017] Beneficial effect: The amount of active substances in the coating is the material basis for ensuring the performance of the coating anode. Considering the coating performance and manufacturing cost, the amount of each layer of the coating after sintering should be maintained at 0.5-0.8 mg / cm 2 , preferably 0.5 mg / cm 2 The coating is formed by spraying, drying and sintering the coating liquid layer by layer, and its main component is a mixture of active oxides of Ir, Ru and Co. Too little coating amount cannot guarantee the electrode performance, and too much coating amount cannot fully exert the performance of the material and is costly.

[0018] Preferably, the coating method is spraying.

[0019] Beneficial effects: Common coating methods in the prior art include immersion, brushing, conventional spraying, plasma spraying, electrochemical treatment, etc. The immersion and brushing methods have simple processes, simple equipment, and strong operability, but cannot guarantee the uniformity of the coating; plasma spraying and electrochemical treatment equipment have high requirements and high costs, and this process also requires a subsequent heat treatment process. The thermal shrinkage and chemical reaction of the material will change the final structure of the coating; conventional spraying technology is mature and relatively easy to operate. The coating liquid is atomized by high-pressure and high-speed airflow and evenly dispersed on the electrode surface to maintain the uniformity of the coating liquid distribution with high efficiency and simple operation.

[0020] Preferably, the sol-gel method comprises the following steps:

[0021] (1) adding a mixed solution of citric acid and ethylene glycol to a mixed solution of ruthenium trichloride and chloroiridic acid, then dropwise adding water and hydrochloric acid and performing ultrasonic treatment to obtain a mixed colloidal solution;

[0022] (2) Adding a colloidal solution of tetrabutyl titanate and a colloidal solution of cobalt chloride to the mixed colloidal solution, performing ultrasonic mixing, and then allowing the mixed solution to stand.

[0023] Beneficial effects: The present invention uses citric acid as a complexing agent in the process of preparing the sol-gel, which can control the concentration of metal ions and play a dispersing role. Ethylene glycol provides -OH groups in the citric acid sol system, plays a dispersing and solvent role, and can also be used as a stabilizer to ensure the stability of the sol. By adjusting the ratio of the two, a sol-gel with high dispersibility and high stability can be prepared to ensure the uniform mixing of elements such as Ir and Ru, and finally obtain a titanium anode coating with uniform composition. Adding a colloidal solution of tetrabutyl titanate and a colloidal solution of cobalt chloride and ultrasonic treatment can achieve full mixing of effective substances in the coating liquid, ensuring the uniformity and stability of the coating liquid.

[0024] Preferably, the mixed solution of ruthenium trichloride and chloroiridic acid in step (1) is obtained by dissolving ruthenium trichloride and chloroiridic acid in anhydrous ethanol and subjecting the mixture to ultrasonic treatment for 10 minutes; and / or,

[0025] The mixed solution of citric acid and ethylene glycol is obtained by dissolving citric acid and ethylene glycol in anhydrous ethanol and then ultrasonically treating the mixture for 10 minutes.

[0026] Beneficial effects: Using citric acid as a complexing agent in the sol-gel preparation process can control the concentration of metal ions and play a dispersing role. Ethylene glycol provides -OH groups in the citric acid sol system, plays a dispersing and solvent role, and can also serve as a stabilizer to ensure the stability of the sol. By adjusting the ratio of the two, a sol-gel with high dispersibility and high stability can be prepared, ensuring the uniform mixing of elements such as Ir and Ru, and finally obtaining a titanium anode coating with uniform composition.

[0027] Preferably, the colloidal solution of tetrabutyl titanate in step (2) is obtained by adding citric acid, ethylene glycol and hydrochloric acid to a tetrabutyl titanate solution and subjecting it to ultrasonic treatment; and / or,

[0028] The cobalt chloride colloidal solution is obtained by adding citric acid, ethylene glycol and hydrochloric acid into a cobalt chloride solution and performing ultrasonic treatment.

[0029] More preferably, the concentration of the tetrabutyl titanate solution is 10 g / L;

[0030] The concentration of the cobalt chloride solution is 10 g / L.

[0031] Preferably, the calcination temperature is 460-480° C. and the calcination time is 40-80 min.

[0032] Beneficial effects: The concentration of tetrabutyl titanate solution and cobalt chloride solution is selected to be 10g / L mainly to control the total amount of the mixed coating solution and prevent too much or too little coating solution. At 460-480℃, chemical reactions can occur in the coating to generate corresponding oxides. If the temperature is too low, the reaction efficiency is low and the crystal structure of the generated substance is not complete. The higher the temperature, the higher the energy consumption and the greater the risk of side reactions. Keeping the temperature for a certain period of time under this calcination temperature condition effectively ensures the integrity of the product structure and production efficiency.

[0033] Application of a composite coating electrode in zinc electrowinning.

[0034] Beneficial effects: The coated titanium anode of the present invention is mainly used in the zinc electrowinning industry, replacing the currently commonly used lead-silver alloy anode, and solving the problems of lead pollution, short electrode life, easy deformation of the electrode, high energy consumption, etc. of the lead-silver alloy anode.

[0035] Compared with the prior art, the present invention has the following advantages and technical effects:

[0036] The present invention designs a titanium anode plate with a brand-new composite structure, which is composed of a titanium substrate, a substrate bonding layer, an intermediate active layer and a surface active layer. The substrate bonding layer, the intermediate active layer and the surface active layer are all composed of oxides of Ti, Ir, Ru and Co, but the proportions of each layer are different, and each metal oxide plays a different matching role. Compared with the traditional brushing coating method, the spraying method is more evenly distributed, and a small amount of multiple times can be controlled. The obtained coating is dense and uniform, not easy to be corroded and peeled off, and the current efficiency and corrosion resistance of the titanium anode plate are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0038] Figure 1 The graph is a test result of the composite coating electrode polarization curve obtained in Examples 1-5 and Comparative Example 1;

[0039] Wherein, A is Example 1, B is Example 2, C is Example 3, D is Example 4, and E is Example 5;

[0040] Figure 2 The graph is a test result of the composite coating electrode polarization curve obtained in Examples 1-5 and Comparative Example 1;

[0041] Wherein, A is Example 1, B is Example 2, C is Example 3, D is Example 4, and E is Example 5;

[0042] Figure 3The graph is a test result of zinc electrowinning of the composite coating electrode obtained in Examples 1-5 and Comparative Example 1;

[0043] Among them, A is Example 1, B is Example 2, C is Example 3, D is Example 4, and E is Example 5. DETAILED DESCRIPTION

[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0046] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;

[0047] The titanium substrate is: a TA2 titanium plate with a size of 30 mm × 10 mm × 3 mm. The titanium plate is polished with sandpaper to remove the surface oxide layer, and the polished titanium plate is placed in a 5% Na2CO3 solution at 60°C for 1 hour. Then, the alkali-washed titanium plate is rinsed with deionized water and placed in a 10% oxalic acid solution for etching at a slightly boiling state for 2.5 hours. Finally, it is ultrasonically treated for 10 minutes, fished out and rinsed with deionized water, dried, and immersed in anhydrous ethanol for use.

[0048] The hydrochloric acid used had a concentration of 36-38%, purchased from Chengdu Kelong Chemical Reagent Factory;

[0049] Ruthenium trichloride (containing 40% Ru) was purchased from Kunming Boxi Metal Materials Co., Ltd.;

[0050] Chloroiridic acid (containing 35% Ir) was purchased from Kunming Boxi Metal Materials Co., Ltd.

[0051] Cobalt chloride (analytical grade) was purchased from Xilong Chemical Co., Ltd.

[0052] Tetrabutyl titanate (analytical grade) was purchased from Xilong Chemical Co., Ltd.

[0053] Oxalic acid (analytical grade) was purchased from Xilong Chemical Co., Ltd.

[0054] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.

[0055] In the following embodiments, due to the certain loss of the coating liquid during the coating preparation process, the molar ratio of Ir, Ru, Ti and Co raw materials in the coating preparation process is not exactly the same as the molar ratio of Ir / Ru / Ti / Co in the coating. This is a normal phenomenon, and those skilled in the art can adjust the amount of raw materials added to the coating liquid according to conventional technical means to obtain a coating with a specified Ir / Ru / Ti / Co molar ratio.

[0056] Example 1

[0057] A method for preparing a composite coating electrode comprises the following steps:

[0058] 1. Preparation of substrate bonding layer coating liquid:

[0059] (1-1) According to the design of the Ir / Ru molar ratio of the coating to be 0.7:0.3, 0.00053 g of ruthenium trichloride and 0.00278 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0060] (1-2) 1 g of citric acid and 5 mL of ethylene glycol were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 2;

[0061] (1-3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 4 hours to obtain a brown colloidal solution, and Liquid No. 3 was obtained;

[0062] (1-4) According to the designed coating Ir / Ru / Ti molar ratio of 0.7:0.3:2, tetrabutyl titanate was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 minutes. Then, a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain liquid No. 4;

[0063] According to the designed coating Ir / Ru / Ti / Co molar ratio of 0.7:0.3:2:0.5, cobalt chloride was weighed and dissolved in 5 mL of anhydrous ethanol, ultrasonicated for 10 minutes, and then a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 5;

[0064] (1-5) Slowly adding liquid No. 4 and liquid No. 5 to liquid No. 3 under ultrasonic conditions for 1 hour, and standing for more than 38 hours to obtain a substrate bonding layer coating liquid;

[0065] 2. Preparation of intermediate active layer coating solution

[0066] (2-1) According to the design of the Ir / Ru molar ratio of the coating to be 3:3, 0.00129 g of ruthenium trichloride and 0.00288 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0067] (2-2) 1 g of citric acid and 5 mL of ethylene glycol were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 2;

[0068] (2-3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise. The mixture was ultrasonicated for 4 hours to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0069] (2-4) According to the designed coating Ir / Ru / Ti molar ratio of 3:3:1, tetrabutyl titanate was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 min. Then, a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 4;

[0070] According to the designed coating Ir / Ru / Ti / Co molar ratio of 3:3:1:4, cobalt chloride was weighed and dissolved in 5 mL of anhydrous ethanol, ultrasonicated for 10 minutes, and then a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 5;

[0071] (2-5) Slowly adding liquid No. 4 and liquid No. 5 to liquid No. 3 under ultrasonic conditions for 1 hour, and leaving the mixture to stand for more than 38 hours to obtain an intermediate active layer coating solution;

[0072] 3. Preparation of Surface Active Layer Coating Solution

[0073] (3-1) According to the design of the Ir / Ru molar ratio of the coating to be 5:3, 0.00123 g of ruthenium trichloride and 0.00461 g of chloroiridic acid were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 1;

[0074] (3-2) 1 g of citric acid and 5 mL of ethylene glycol were dissolved in 5 mL of anhydrous ethanol and ultrasonically treated for 10 minutes to obtain solution No. 2;

[0075] (3-3) Liquid No. 2 was slowly dripped into Liquid No. 1, and 5 mL of deionized water and 1 mL of hydrochloric acid were added dropwise while continuing to stir. The mixture was ultrasonicated for 4 hours to obtain a brown colloidal solution, thereby obtaining Liquid No. 3;

[0076] (3-4) According to the designed coating Ir / Ru / Ti molar ratio of 5:3:0.5, tetrabutyl titanate was weighed and dissolved in 5 mL of anhydrous ethanol, and ultrasonicated for 10 min. Then, a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 4;

[0077] According to the designed coating Ir / Ru / Ti / Co molar ratio of 5:3:0.5:2, cobalt chloride was weighed and dissolved in 5 mL of anhydrous ethanol, ultrasonicated for 10 minutes, and then a mixed solution of 1 g of citric acid and 5 mL of ethylene glycol and 1 mL of hydrochloric acid were added, and ultrasonicated for 1 hour to obtain solution No. 5;

[0078] (3-5) Slowly adding liquid No. 4 and liquid No. 5 to liquid No. 3 under ultrasonic conditions for 1 hour, and allowing to stand for more than 38 hours to obtain a surfactant coating solution;

[0079] 4. Preparation of Composite Coating Electrodes

[0080] The above substrate bonding layer coating liquid was sprayed on the treated titanium plate with a coating amount of 1.5 mg / cm 2 , then placed under an infrared lamp for drying, and then sintered at 460°C for 10 minutes, and then sprayed with the intermediate active layer coating liquid on the obtained substrate bonding layer, with a coating amount of 1.5 mg / cm 2 , dried under an infrared lamp, and then sintered at 460°C for 10 minutes. Finally, the surface active layer coating liquid was sprayed on the intermediate active layer with a coating amount of 1.5 mg / cm 2 , dried under an infrared lamp, and then sintered at 460°C for 60 minutes to obtain a composite coating electrode.

[0081] Example 2

[0082] A method for preparing a composite coating electrode, which is different from Example 1 in that:

[0083] 1. Preparation of substrate bonding layer coating liquid:

[0084] The added mass of ruthenium trichloride in step (1-1) remains unchanged, and the Ir / Ru molar ratio is 0.7:0.3;

[0085] In step (1-4), the molar ratio of Ir / Ru / Ti is 0.7:0.3:2.5;

[0086] The molar ratio of Ir / Ru / Ti / Co is 0.7:0.3:2.5:0.7;

[0087] 2. Preparation of intermediate active layer coating solution

[0088] The added mass of ruthenium trichloride in step (2-1) remains unchanged, and the Ir / Ru molar ratio is 2:3;

[0089] The molar ratio of Ir / Ru / Ti in step (2-4) is 2:3:1;

[0090] The molar ratio of Ir / Ru / Ti / Co is 2:3:1:5;

[0091] 3. Preparation of Surface Active Layer Coating Solution

[0092] The added mass of ruthenium trichloride in step (3-1) remains unchanged, and the Ir / Ru molar ratio is 5:3;

[0093] The molar ratio of Ir / Ru / Ti in step (3-4) is 5:3:0.5;

[0094] The molar ratio of Ir / Ru / Ti / Co is 5:3:0.5:2;

[0095] 4. Preparation of Composite Coating Electrodes

[0096] The above substrate bonding layer coating liquid was sprayed on the treated titanium plate with a coating amount of 1.5 mg / cm 2 , then placed under an infrared lamp for drying, and then sintered at 480°C for 60 minutes, and then sprayed with the intermediate active layer coating liquid on the obtained substrate bonding layer, with a coating amount of 1.5 mg / cm 2 , dried under an infrared lamp, and then sintered at 480°C for 80 minutes. Finally, the surface active layer coating liquid was sprayed on the intermediate active layer with a coating amount of 1.5 mg / cm 2 , dried under an infrared lamp, and then sintered at 480°C for 60 minutes to obtain a composite coating electrode.

[0097] The remaining process steps and parameters are the same as those in Example 1.

[0098] Example 3

[0099] A method for preparing a composite coating electrode, which is different from Example 1 in that:

[0100] 1. Preparation of substrate bonding layer coating liquid:

[0101] The added mass of ruthenium trichloride in step (1-1) remains unchanged, and the Ir / Ru molar ratio is 0.7:0.3;

[0102] In step (1-4), the molar ratio of Ir / Ru / Ti is 0.7:0.3:2;

[0103] The molar ratio of Ir / Ru / Ti / Co is 0.7:0.3:2:0.6;

[0104] 2. Preparation of intermediate active layer coating solution

[0105] The added mass of ruthenium trichloride in step (2-1) remains unchanged, and the Ir / Ru molar ratio is 3:3;

[0106] The molar ratio of Ir / Ru / Ti in step (2-4) is 3:3:1;

[0107] The molar ratio of Ir / Ru / Ti / Co is 3:3:1:4;

[0108] 3. Preparation of Surface Active Layer Coating Solution

[0109] The added mass of ruthenium trichloride in step (3-1) remains unchanged, and the Ir / Ru molar ratio is 5:3;

[0110] The molar ratio of Ir / Ru / Ti in step (3-4) is 5:3:0.5;

[0111] The molar ratio of Ir / Ru / Ti / Co is 5:3:0.5:2;

[0112] 4. Preparation of Composite Coating Electrodes

[0113] The above substrate bonding layer coating liquid was sprayed on the treated titanium plate with a coating amount of 1.5 mg / cm 2 , then placed under an infrared lamp for drying, and then sintered at 480°C for 60 minutes, and then sprayed with the intermediate active layer coating liquid on the obtained substrate bonding layer, with a coating amount of 1.5 mg / cm 2 , dried under an infrared lamp, and then sintered at 480°C for 60 minutes. Finally, the surface active layer coating liquid was sprayed on the obtained intermediate active layer with a coating amount of 1.5 mg / cm 2 , dried under an infrared lamp, and then sintered at 480°C for 60 minutes to obtain a composite coating electrode.

[0114] The remaining process steps and parameters are the same as those in Example 1.

[0115] Example 4

[0116] A method for preparing a composite coating electrode, which is different from Example 1 in that:

[0117] 1. Preparation of substrate bonding layer coating liquid:

[0118] The added mass of ruthenium trichloride in step (1-1) remains unchanged, and the Ir / Ru molar ratio is 0.7:0.3;

[0119] In step (1-4), the molar ratio of Ir / Ru / Ti is 0.7:0.3:2;

[0120] The molar ratio of Ir / Ru / Ti / Co is 0.7:0.3:2:0.7;

[0121] 2. Preparation of intermediate active layer coating solution

[0122] The added mass of ruthenium trichloride in step (2-1) remains unchanged, and the Ir / Ru molar ratio is 2:3;

[0123] In step (2-4), the molar ratio of Ir / Ru / Ti is 2:3:0.8;

[0124] The molar ratio of Ir / Ru / Ti / Co is 2:3:0.8:5;

[0125] 3. Preparation of Surface Active Layer Coating Solution

[0126] The added mass of ruthenium trichloride in step (3-1) remains unchanged, and the Ir / Ru molar ratio is 5:3;

[0127] The molar ratio of Ir / Ru / Ti in step (3-4) is 5:3:0.5;

[0128] The molar ratio of Ir / Ru / Ti / Co is 5:3:0.5:2;

[0129] 4. Preparation of Composite Coating Electrodes

[0130] The above substrate bonding layer coating liquid was sprayed on the treated titanium plate with a coating amount of 1.5 mg / cm 2 , then placed under an infrared lamp for drying, and then sintered at 460°C for 60 minutes, and then sprayed with the intermediate active layer coating liquid on the obtained substrate bonding layer, with a coating amount of 1.5 mg / cm 2 , dried under an infrared lamp, and then sintered at 480°C for 60 minutes. Finally, the surface active layer coating liquid was sprayed on the obtained intermediate active layer with a coating amount of 1.5 mg / cm 2 , dried under an infrared lamp, and then sintered at 480°C for 60 minutes to obtain a composite coating electrode.

[0131] The remaining process steps and parameters are the same as those in Example 1.

[0132] Example 5

[0133] A method for preparing a composite coating electrode, which is different from Example 1 in that:

[0134] 1. Preparation of substrate bonding layer coating liquid:

[0135] The added mass of ruthenium trichloride in step (1-1) remains unchanged, and the Ir / Ru molar ratio is 0.6:0.4;

[0136] In step (1-4), the molar ratio of Ir / Ru / Ti is 0.6:0.4:1.5;

[0137] The molar ratio of Ir / Ru / Ti / Co is 0.6:0.4:1.5:1;

[0138] 2. Preparation of intermediate active layer coating solution

[0139] The added mass of ruthenium trichloride in step (2-1) remains unchanged, and the Ir / Ru molar ratio is 2.5:3;

[0140] The molar ratio of Ir / Ru / Ti in step (2-4) is 2.5:3:1;

[0141] The molar ratio of Ir / Ru / Ti / Co is 2.5:3:1:4.5;

[0142] 3. Preparation of Surface Active Layer Coating Solution

[0143] The added mass of ruthenium trichloride in step (3-1) remains unchanged, and the Ir / Ru molar ratio is 5:3;

[0144] The molar ratio of Ir / Ru / Ti in step (3-4) is 5:3:0.4;

[0145] The molar ratio of Ir / Ru / Ti / Co is 5:3:0.4:2;

[0146] 4. Preparation of Composite Coating Electrodes

[0147] The above substrate bonding layer coating liquid was sprayed on the treated titanium plate with a coating amount of 1.5 mg / cm 2 , then placed under an infrared lamp for drying, and then sintered at 460°C for 60 minutes, and then sprayed with the intermediate active layer coating liquid on the obtained substrate bonding layer, with a coating amount of 1.5 mg / cm 2 , dried under an infrared lamp, and then sintered at 480°C for 60 minutes. Finally, the surface active layer coating liquid was sprayed on the obtained intermediate active layer with a coating amount of 1.5 mg / cm 2 , dried under an infrared lamp, and then sintered at 480°C for 60 minutes to obtain a composite coating electrode.

[0148] The remaining process steps and parameters are the same as those in Example 1.

[0149] Comparative Example 1

[0150] A method for preparing a Pb-Ag (1%) electrode comprises the following steps:

[0151] Heat 1# lead (purity ≥ 99.994%) to 350°C and pure silver (purity ≥ 99.99) to 1000°C, then mix them thoroughly according to Pb:Ag=99:1, pour them into a designated mold, and make them after cooling, surface treatment and machining.

[0152] Comparative Example 2

[0153] A method for preparing a composite coating electrode, which is different from Example 1 in that:

[0154] The substrate bonding layer is not included.

[0155] The remaining process steps and parameters are the same as those in Example 1.

[0156] Comparative Example 3

[0157] A method for preparing a composite coating electrode, which is different from Example 1 in that:

[0158] The intermediate active layer is not included.

[0159] The remaining process steps and parameters are the same as those in Example 1.

[0160] Comparative Example 4

[0161] A method for preparing a composite coating electrode, which is different from Example 1 in that:

[0162] The surfactant layer is not included.

[0163] The remaining process steps and parameters are the same as those in Example 1.

[0164] Technical effects:

[0165] The electrochemical treatment performance test was carried out on the composite coating electrodes obtained in Examples 1-5 and the Pb-Ag (1%) electrode obtained in Comparative Example 1, and the method was as follows: three 1 cm×1 cm composite coating electrode samples were cut from the composite coating electrode, and the first sample was inserted into an electrolytic cell containing a 0.5 mol / L sulfuric acid solution with a titanium sheet cathode and a saturated calomel electrode; the second sample was inserted into an electrolytic cell containing a 1 mol / L sulfuric acid solution with a titanium sheet cathode, and a DC power supply was used to carry out an enhanced life test experiment (the electrode was considered to have failed when the cell voltage increased by 10 V compared with the initial stage), the electrolyte temperature was 30°C, and the anode current density was 20000 A / m 2 After electrolysis for 1 hour, the sulfuric acid concentration of the electrolyte was measured by chemical analysis (to calculate the oxygen evolution efficiency); the third portion and the aluminum cathode were inserted into an electrolyte containing 55g / L Zn2SO4 solution and an acidity of H2SO4 165g / L. The electrolytic cell temperature was 38℃~40℃, the electrolysis time was 24h, the electrolyte flow rate was 470mL / h, and the zinc electrolysis experiment was carried out using a DC power supply constant current. The anode current density was 10000A / m 2 , the anode current efficiency is calculated by formula (1).

[0166]

[0167] Where: η i represents cathode current efficiency, %; m represents the actual zinc production in time t, g; I represents the current passing between the cathode and cathode, A; t represents the electrolysis time, h; n represents the number of electrolysis cells; q represents the electrochemical equivalent of zinc, which is 1.220 g / (A·h).

[0168] The results of the electrochemical performance test and the enhanced life test are shown in Table 1; the results of the zinc electrowinning test are shown in Table 2.

[0169] Table 1 Electrochemical performance test of coated titanium anode

[0170] Oxygen evolution potential (mV) Strengthening life (h) Oxygen evolution efficiency (%) Example 1 828.4 145 90.56 Example 2 826.5 147 91.01 Example 3 827.6 143 90.83 Example 4 835.8 143 90.85 Example 5 818.9 146 91.12 Comparative Example 1 912.6 128 88.95 Comparative Example 2 836.2 136 90.10 Comparative Example 3 846.7 140 90.22 Comparative Example 4 831.5 116 90.06

[0171] As can be seen from Table 1, the oxygen evolution potential of the composite coating electrode prepared by the method of Examples 1-5 of the present invention is nearly 100 mV lower than that of the traditional Pb-Ag (1%) anode, the enhanced life is more than 140 hours, and the oxygen evolution efficiency is greater than 90%. The above three important parameters are all better than the Pb-Ag (1%) anode obtained in Comparative Example 1.

[0172] Table 2 Voltage and current efficiency test of coated titanium anode zinc electroplating bath

[0173] Average cell voltage (V) Current efficiency (%) Example 1 3.0604 88.76 Example 2 2.9460 90.01 Example 3 2.9204 90.63 Example 4 2.9328 90.26 Example 5 2.9448 90.12 Comparative Example 1 3.2463 88.15 Comparative Example 2 3.0147 89.12 Comparative Example 3 2.9826 89.21 Comparative Example 4 2.9563 88.05

[0174] It can be seen from Table 2 that the composite coating electrode prepared by the method of the present invention has low cell pressure, small change and high current efficiency during zinc electrowinning. The above two important parameters are better than the Pb-Ag (1%) anode obtained in Comparative Example 1.

[0175] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A composite coating electrode, characterized in that: The invention comprises a stacked titanium substrate, a substrate bonding layer, an intermediate active layer and a surface active layer, wherein the substrate bonding layer, the intermediate active layer and the surface active layer all comprise oxides of Ti, Ir, Ru and Co.

2. A composite coating electrode according to claim 1, characterized in that: The molar ratio of Ti:Ir:Ru:Co in the substrate bonding layer is (1.5-3):(0.5-0.7):(0.3-0.5):(0.5-1).

3. A composite coating electrode according to claim 1, characterized in that: The molar ratio of Ti:Ir:Ru:Co in the intermediate active layer is (1-1.5):(2-3):3:(3-5).

4. A composite coating electrode according to claim 1, characterized in that: The molar ratio of Ti:Ir:Ru:Co in the surface active layer is (0.3-0.5):5:3:

2.

5. A method for preparing a composite coating electrode according to any one of claims 1 to 4, characterized in that: The following steps are involved: After preparing the substrate bonding layer coating liquid, the intermediate active layer coating liquid and the surface active layer coating liquid respectively by the sol-gel method, the substrate bonding layer coating liquid, the intermediate active layer coating liquid and the surface active layer coating liquid are sequentially coated on the titanium substrate, and calcined after each layer is coated to obtain the composite coating electrode.

6. A composite coating electrode according to claim 5, characterized in that: The coating amount of the substrate bonding layer coating liquid, the intermediate active layer coating liquid and the surface active layer coating liquid before calcination is 1.0-2.0 mg / cm 2 .

7. The method for preparing a composite coating electrode according to claim 5, characterized in that: The sol-gel method comprises the following steps: (1) adding a mixed solution of citric acid and ethylene glycol to a mixed solution of ruthenium trichloride and chloroiridic acid, then dropwise adding water and hydrochloric acid and performing ultrasonic treatment to obtain a mixed colloidal solution; (2) Adding a colloidal solution of tetrabutyl titanate and a colloidal solution of cobalt chloride to the mixed colloidal solution, performing ultrasonic mixing, and then allowing the mixed solution to stand.

8. The method for preparing a composite coating electrode according to claim 7, characterized in that: The mixed solution of ruthenium trichloride and chloroiridic acid in step (1) is obtained by dissolving ruthenium trichloride and chloroiridic acid in anhydrous ethanol and subjecting the mixture to ultrasonic treatment for 10 minutes; and / or, The mixed solution of citric acid and ethylene glycol is obtained by dissolving citric acid and ethylene glycol in anhydrous ethanol and then ultrasonically treating the mixture for 10 minutes.

9. The method for preparing a composite coating electrode according to claim 5, characterized in that: The calcination temperature is 460-480° C. and the calcination time is 40-80 min.

10. Use of a composite coating electrode as claimed in any one of claims 1 to 4 in zinc electrowinning.